Konsumentens dilemma - Lönn, Mikaela (2004)
A majority of Swedish consumers have a positive attitude towards organic production and the number of organic products on the market is increasing. Despite these positive trends, there are still relatively few consumers who choose to buy organic produced products. According to statistics, only 3% of the total sales of food consist of organic products.